Content validation of a new measure of patient-reported barriers to antiretroviral therapy adherence, the I-Score: results from a Delphi study - Kim Engler; Serge Vicente; Kedar K. V. Mate; David Lessard; Sara Ahmed; Bertrand Lebouché (SpringerOpen, 2022)
Abstract Background Over a third of people living with HIV (PLHIV) have suboptimal adherence to antiretroviral therapy (ART). Measures of barriers to ART adherence often lack comprehensiveness. To help manage ART adherence barriers in HIV care, we are developing a new patient-reported outcome measure (PROM) of these barriers (the I-Score). Methods We assessed the content validity of 100 items (distinct barriers) to retain only those most relevant to both PLHIV and HIV health/social service providers. A web-based Delphi was conducted in Canada and France, collecting data from December 2018 to October 2019. Items were evaluated on relevance (the combined rated importance and actionability for HIV care of items among both PLHIV and providers); comprehensibility (rated item clarity); comprehensiveness (examined against our conceptual framework); cross-cultural equivalence (based on comparisons by questionnaire language (English, French) and country of residence). Pearson's chi-square tests were used for comparisons by language, country, gender, and stakeholder group (PLHIV, providers). Results Panelists included 40 PLHIV and 57 providers (66% response rate). Thirty-one items were retained based on consensus thresholds for relevance (minimum: 50% for PLHIV, 60% for providers) and showed good comprehensibility and comprehensiveness, when compared to our conceptual framework (representation of: 6/6 domains, 15/20 subdomains). No significant difference in relevance based on language or country was found among retained items, suggestive of cross-cultural equivalence. Among all 100 items, only 6 significant differences on relevance were observed for gender. For 62 items, the relevance ratings of PLHIV and providers differed significantly, with providers showing greater endorsement of all items but one. Discussion The Delphi led to a much-needed item reduction. Remaining items highlight the panel's multidimensional priorities for the PROM on ART adherence barriers, with few, if any, differences by language, country, and gender. While the analyses may lack generalizability and power, the sample size is considered adequate for a PROM validation study. Conclusion Retained items showed good content validity. The different patterns of item endorsement observed underscore the utility of engaging multiple stakeholder groups in PROM development for use in clinical practice. The greater endorsement of items by providers versus patients merits further investigation, including the implications of such differentials for measure development.